THE CONCEPT OF ECOLOGICAL MIND AND ECOLOGICAL CULTURE (British Journal of Global Ecology and Sustainable Development, 2024)
Ecological knowledge serves as the basis for ecological thinking. The article outlines basic concepts that describe ecological thinking.